Stability of the principles of minimal specificity and maximal buoyancy - Thanh, Do Van (Journal of Computer Science and Cybernetics, 2016)
The aim of  this paper is to investigate an use of  the principles of minimal Specificity and maximal Buoyancy (MB) proposed by R.R.Yager and to introduced some conditions of a set of possibility distributions and  weights which guarantee uniqueness of  possibility distribution selected by the use of these principles from a given set of  distributions.